(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the linguistic situation formed in Uzbekistan during the years of independence, the main directions of language policy, the role of the state language in society and its stages of development. Also, the functional capabilities of the Uzbek language in multilingual conditions, the impact of globalization on the language, and changes in the writing system are scientifically covered. As a result of the study, scientific conclusions are put forward on further improving the linguistic environment.